2020
DOI: 10.1016/j.nicl.2020.102349
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the metabolic networks of temporal lobe epilepsy patients: A graph theoretical analysis using FDG-PET

Abstract: Highlights The aim of this study is to investigate changes in metabolic networks in patients with drug-resistant TLE. TLE patients with HS show alterations of metabolic connectivity compared to those without HS. This may represent distinct epileptic networks in TLE patients with HS versus those without HS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…Thus, these results indicate that TLE patients with HS carry a more disconnected functional brain network with a decreased integration than those without HS. The results are consistent with our recent work, demonstrating more severe alterations in metabolic networks based on FDG‐PET in TLE patients with HS than in those without HS and healthy controls 21 . Furthermore, Coan et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, these results indicate that TLE patients with HS carry a more disconnected functional brain network with a decreased integration than those without HS. The results are consistent with our recent work, demonstrating more severe alterations in metabolic networks based on FDG‐PET in TLE patients with HS than in those without HS and healthy controls 21 . Furthermore, Coan et al.…”
Section: Discussionsupporting
confidence: 93%
“…Next, using the BRAPH program, we created a weighted connectivity matrix based on the partial correlation and the CBF of the regions with corrections of covariates, including age and sex, and calculated the global and local network measures from the connectivity matrix. We already described the detailed method to obtain the network measures using BRAPH program in our previous studies 21,22 …”
Section: Methodsmentioning
confidence: 99%
“…Brain networks constructed from regional covariance estimation based on PET have gained particular attention in terms of metabolic networks. Recently, we have demonstrated changes in metabolic networks based on FDG‐PET using graph theoretical analysis in TLE patients, and found more severe alterations in TLE patients with HS than in those without HS and healthy controls 18 . Although some studies have suggested that graph theoretical analysis to reveal brain networks using several modalities, such as MRI, EEG, or MEG in TLE patients with HS, can predict seizure free following surgery, 19–21 there have been no studies regarding metabolic networks based on FDG‐PET for predicting surgical outcomes at the group level.…”
Section: Introductionmentioning
confidence: 99%
“…The term metabolic connectivity refers to interrelations between metabolic (FDG) measurements in different brain regions [1]. This approach was shown to yield valuable knowledge on substrates of cognitive reserve [2,3], working memory [4,5], impulse control [6], as well as on pathophysiology and diagnosis of neurodegenerative [7][8][9][10] and non-neurodegenerative disorders [11,12]. However, it is still unclear how MC is related to actual structural connectivity, i.e., connectivity through white matter fiber tracts.…”
Section: Introductionmentioning
confidence: 99%